2015
DOI: 10.1556/2006.4.2015.030
|View full text |Cite
|
Sign up to set email alerts
|

The role of negative mood states and consequences of hypersexual behaviours in predicting hypersexuality among university students

Abstract: Background and AimsThe issue of whether hypersexual behaviours exist among university students is controversial because many of these individuals engage in sexual exploration during their time at university. To date, little is known about the correlates of hypersexual behaviours among university students in the UK. Therefore, the aims of this exploratory study were two-fold. Firstly, to explore and establish the correlates of hypersexual behaviours, and secondly, to investigate whether hypersexuality among uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Their social nature may also increase the potential of more sexual opportunities (e.g., socializing at parties, leisure events, etc.). The positive relationship with neuroticism also corroborates findings from previous studies (Pinto et al, 2013 ; Rettenberger et al, 2016 ; Walton et al, 2017 ), and is congruent with the assumption that sex has an anxiolytic effect (Coleman, 1992 ), and that engaging in sexual activities may function as an escape from dysphoric feelings (O'Brien and DeLongis, 1996 ; Dhuffar et al, 2015 ; Wéry et al, 2016b ). Intellect/imagination also had a positive relationship with addictive sexual behavior.…”
Section: Discussionsupporting
confidence: 86%
“…Their social nature may also increase the potential of more sexual opportunities (e.g., socializing at parties, leisure events, etc.). The positive relationship with neuroticism also corroborates findings from previous studies (Pinto et al, 2013 ; Rettenberger et al, 2016 ; Walton et al, 2017 ), and is congruent with the assumption that sex has an anxiolytic effect (Coleman, 1992 ), and that engaging in sexual activities may function as an escape from dysphoric feelings (O'Brien and DeLongis, 1996 ; Dhuffar et al, 2015 ; Wéry et al, 2016b ). Intellect/imagination also had a positive relationship with addictive sexual behavior.…”
Section: Discussionsupporting
confidence: 86%
“…Another study also found that among heterosexual couples, the increasing likelihood of regrettable sexual behaviors in negative mood states was a signi cant predictor of sexual in delity [44]. Furthermore, people with hypersexual behaviors were more likely to experience shame [45][46][47].…”
Section: Discussionmentioning
confidence: 91%
“…As existed in IGD, these disorders have also been characterized to varying extents by difficulties in emotional regulation. As mood may affect cognitive functioning, studies should also examine the broader impact of decreased FC within the DMN in healthy and psychiatric populations (Dhuffar et al, 2015;Foland-Ross et al, 2012;Jackson et al, 2016;Prossin et al, 2016). As mindfulness meditation training may increase DMN FC (Creswell et al, 2016), future studies may also examine the extent to which such interventions may be helpful for psychiatric conditions and operate through changes in FC of the DMN.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to emotions, moods may be less intense, less specific, and less likely to be triggered by a particular event (Jackson and Arlegui-Prieto, 2016). Moods are typically described as having either a good/positive or bad/negative valence, and moods, especially negative ones, have important implications for human mental and psychological wellbeing (Dhuffar et al, 2015;Foland-Ross et al, 2012;Jackson et al, 2016;Prossin et al, 2016). It is possible that the FC of the DMN may relate to mood states.…”
Section: Introductionmentioning
confidence: 99%